Development of genomic resources for the narrow-leafed lupin (Lupinus angustifolius): construction of a bacterial artificial chromosome (BAC) library and BAC-end sequencing - Gao, L.; Hane, James; Kamphuis, L.; Foley, R.; Shi, B.; Atkins, C.; Singh, K. (Biomed Central Ltd, 2011)
Background: Lupinus angustifolius L, also known as narrow-leafed lupin (NLL), is becoming an important grain legume crop that is valuable for sustainable farming and is becoming recognised as a potential human health food. Recent interest is being directed at NLL to improve grain production, disease and pest management and health benefits of the grain. However, studies have been hindered by a lack of extensive genomic resources for the species.Results: A NLL BAC library was constructed consisting of 111,360 clones with an average insert size of 99.7 Kbp from cv Tanjil. The library has approximately 12 × genome coverage. Both ends of 9600 randomly selected BAC clones were sequenced to generate 13985 BAC end-sequences (BESs), covering approximately 1% of the NLL genome. These BESs permitted a preliminary characterisation of the NLL genome such as organisation and composition, with the BESs having approximately 39% G:C content, 16.6% repetitive DNA and 5.4% putative gene-encoding regions. From the BESs 9966 simple sequence repeat (SSR) motifs were identified and some of these are shown to be potential markers.Conclusions: The NLL BAC library and BAC-end sequences are powerful resources for genetic and genomic research on lupin. These resources will provide a robust platform for future high-resolution mapping, map-based cloning, comparative genomics and assembly of whole-genome sequencing data for the species.